Computer Vision Syndrome (CVS) among secondary school students in Selangor / Sabrina Subri and Nurin Syahmina Mohd Naziran - Subri, Sabrina; Mohd Naziran, Nurin Syahmina (Faculty of Health Sciences, Universiti Teknologi MARA, 2023)
Computer Vision Syndrome (CVS) is a group of ocular and vision-related symptoms that manifest after prolonged digital device usage. With increasing use of digital devices especially among teenagers, this study aimed to investigate the prevalence of CVS among secondary school students in Selangor and their level of awareness about this condition. In this cross-sectional study, CVS-Q (Computer Vision Syndrome Questionnaire) (Seguí et al., 2015) was distributed both online and offline to secondary school students in Selangor. The questionnaire included demographic information, general and ocular health conditions, and questions on CVS to determine their awareness about the condition and symptoms of CVS that they have experienced. A total of 202 students, aged between 13 and 18 years, 72.3% of whom were females participated in the study. About 50% of the total participants were reported to have CVS. The most prevalent symptoms experienced by the students were headache (69%) and itchy eyes (69%), followed by burning sensation (60%) and watery eyes (59%); whereas seeing halos around objects (24%) was found to be the least reported symptoms experienced by them. 18.8 % of the participants claimed that they were aware of CVS. The chi-square test revealed that CVS was associated with gender (x2 (1) = 8.01, p = 0.005) with females being associated with higher CVS scores. The prevalence of CVS among secondary school students in Selangor is considerably high, with higher CVS symptoms found in female participants. A low level of awareness of CVS warrants health education on this matter among this population.